Removal Of Pollutants Using Nanostructured Tungsten Oxide - Tan, Gang Yang (Universiti Sains Malaysia, 2022)
Tungsten (W) is a popular metallic transition element and its oxide (WOx) can be can found in applications in the field of electrical and electronics, coatings, as well as cosmetic products. In recent years, nanostructured Tungsten Oxide (WO3) has gained particular attention due to its promising properties and applications. Among all the applications, one of those is as a photocatalyst in the degradation of organic pollutants. The objective of this present work is to synthesis nanostructured WO3 by using thermal oxidation method and to also investigate the possibility of MO removal using the synthesized nanostructured WO3. In this research, two methods were studied, which are one-step and two-step thermal oxidation. Several parameters were manipulated to find out the most optimum to synthesize nanostructured WO3, includes the effect of KOH mist flowing time, the effect of thermal oxidation temperatures, the effect of KOH concentration and the effect of surface roughness of the tungsten foil. The characterization techniques used to examine the synthesized samples include FESEM, XRD and EDX. From the result obtained, the nanostructured WO3 with nanowires was successfully synthesized at 600°C in normal air condition without the presence of KOH acts as catalyst. The degradation efficiency of this sample has achieved the highest degradation (85%).